Glagoli na -irati v današnji slovenščini - Žele, Andreja (Slavistična revija, 2011)
The paper treats the status of verbs formed with irati in the contemporary Slovene lexicon and their word-formation and syntactic properties. With respect to verbal aspect some special issuse and questions are noted.
Keywords: glagol; glagolski vid; neologisms; novotvorjenke; Slovene; Slovene language; slovenščina; verb; verbal aspect; verbal neologisms